Design, Fabrication, and Testing of a Microfluidic Device for Thermotaxis and Chemotaxis Assays of Sperm. (December 2018) - Ko, Yong-Jun; Maeng, Joon-Ho; Hwang, Seung Yong; Ahn, Yoomin
Infertile couples needing assisted reproduction are increasing, so a fundamental understanding of motile sperm migration is required. This paper presents an advanced microfluidic device for sperm motion analysis utilizing chemotaxis and thermotaxis simultaneously for the first time. The proposed device is a transparent polydimethylsiloxane- and glass-based microfluidic chip system providing a low-cost, useful, and disposable platform for sperm analysis. The concentration gradient of the chemoattractant (acetylcholine) and the temperature difference are formed along the microchannel. The temperature gradient is generated and controlled by a microheater and microsensor. Thermotactic and chemotactic responses of mouse sperm were examined using the proposed device. Experimental results show that motile mouse sperm are attracted more sensitively under integrated conditions of chemotaxis and thermotaxis rather than individual conditions of chemotaxis and thermotaxis. This sperm analysis device is expected to be a useful tool for the study of mammalian sperm migration and the improvement of artificial insemination techniques.